Metronidazole-Induced Encephalopathy in a 16-Year-Old Girl with Crohn's Disease: Case Report and Review of the Pediatric Literature - Karolina Rybak; Aleksandra Warchoł; Łukasz Drobczyński; Aleksandra Banaszkiewicz (MDPI AG, 2022)
Metronidazole-induced encephalopathy (MIE) is a rare and unpredictable complication that is most commonly reported in adults. Here, we present the case of MIE in a patient treated with rectal, oral, and intravenous metronidazole. This is the first case of MIE reported after suppositories. A 16-year-old girl with Crohn's disease treated with mesalazine and exclusive enteral nutrition was operated on due to perianal fistulas and abscesses. She received oral metronidazole for 25 days and rectal metronidazole for 15 days as an adjuvant before surgery. Moreover, 2.5 g of intravenous metronidazole was administrated during the perioperative period. The second day after the surgery, symptoms of cerebellar syndrome appeared. She presented with an inability to coordinate balance and gait. Although she showed accurate verbal responses, her speech was slow, slurred, and scanning. The finger-nose test was positive. The T2-weighted magnetic resonance imaging revealed an increased symmetrical signal within the dentate nuclei of the cerebellum and in the corpus callosum. The changes were characterized by restricted diffusion. Based on the clinical picture and magnetic resonance imaging findings, MIE was diagnosed. Treatment with metronidazole was discontinued. The cumulative dose of metronidazole that she received for 29 days was 54 g: 38 g p.o., 13.5 g p.r., and 2.5 g i,v. The first symptoms appeared on the 28th day of antibiotic therapy after receiving 52 g of metronidazole. The neurological symptoms resolved after six days; however, three days after the resolution, paresthesia appeared in the distal phalanges of both feet and lasted for approximately two months. Our report highlights that neurologic symptoms related to metronidazole treatment should raise the suspicion of MIE.